Novel, Chiral, and Enantiopure C2‐Symmetric Thioureas Promote Asymmetric Protio‐Pictet‐Spengler Reactions by Anion‐Binding Catalysis. Issue 5 (22nd January 2021) - Retini, Michele; Bartoccini, Francesca; Zappia, Giovanni; Piersanti, Giovanni
Abstract: Although anion‐binding processes are well‐known for their crucial role in molecular recognition, they have only recently been utilized for catalysis. Herein, a new class of chiral, enantiopure C2 ‐symmetrical thioureas that, in combination with 4‐methoxybenzoic acid, promotes the enantioselective protio‐Pictet‐Spengler reaction to provide unprotected tetrahydro‐β‐carbolines in good yields (40–93 %) and moderate‐to‐high enantioselectivities (34–95 % ee) in one step from tryptamine and aldehyde derivatives is described. The formation of a chiral catalyst‐anion complex was explored by 1 H NMR. Abstract : A novel L‐valine‐derived C2 ‐symmetric thiourea catalyst, in combination with 4‐methoxybenzoic acid, promoted the enantioselective reaction of tryptamines with aldehydes (protio‐Pictet‐Spengler reactions) to give the corresponding tetrahydro‐β‐carbolines with good enantioselectivity (up to 95 % ee) by chiral anion‐binding catalysis.